Associations Between Amantadine Usage, Gait, and Cognition in PSP: A post-hoc Analysis of the Davunetide Trial - Dale, Marian L.; Brumbach, Barbara H.; Boxer, Adam L.; Hiller, Amie L. (Frontiers in Neurology, 2020)
Introduction: Amantadine anecdotally improves gait in progressive supranuclear palsy (PSP) but definitive data is lacking. We investigated associations between amantadine usage, gait, cognition, and activities of daily living in 310 subjects with PSP using data from the davunetide trial. Method: We compared baseline demographics, PSP Rating Scale (PSPRS), Repeat Battery for the Assessment of Neuropsychological Status (RBANS), and Schwab and England Activities of Daily Living (SEADL) scores between subjects taking vs not taking amantadine using chi-square tests for categorical variables and independent sample t-tests for continuous variables. Using the general linear model (GLM), we tested whether group status predicted total PSPRS, PSPRS-gait and midline, total RBANS, RBANS-attention, and SEADL before and after the 52-week follow-up. Results: Subjects taking vs not taking amantadine were similar at baseline, except subjects taking amantadine had a higher Clinical Global Impression (CGI) Score (p= 0.01). However, the CGI change score did not differ between groups at week 52 (p= 0.10). Using GLM models (controlling for covariates), we found that subjects taking vs not taking amantadine did not significantly predict total PSPRS, PSPRS-gait and midline, total RBANS, RBANS-attention, or SEADL at baseline, week 52, or the change score between baseline and week 52. Discussion: This post hoc analysis of the davunetide trial did not find an association between amantadine and gait or cognitive measures in PSP, but was not powered to find such a difference. Future studies should still examine amantadine for symptomatic benefit in multiple PSP subtypes.